Kolaborasi Pendekatan Three Smart dan Two Intelligence dalam Mempersiapkan Peserta Didik Menghadapi Revolusi Industri 4.0 (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
The Industrial Revolution 4.0 has brought significant changes to various aspects of human life, including education. The rapid development of digital technology requires educational institutions to prepare students who not only possess academic knowledge but also have the ability to think critically, be creative, communicate, collaborate, and adapt to change. This article aims to analyze the integration of the Three Smart and Two Intelligence approaches as a strategy for preparing students to face the demands of the Industrial Revolution 4.0. This study employed a library research method by examining literature related to the development of the Industrial Revolution, education in the digital era, soft skills development, and student competencies. The findings indicate that the Three Smart approach, consisting of Smart Foundation, Smart Process, and Smart Connectivity, can support students in developing a foundation of knowledge, processing information critically, and building networking and collaboration skills. This approach needs to be balanced with the development of Two Intelligence, particularly interpersonal and intrapersonal intelligence, so that students can understand themselves and others, establish social relationships, and develop self-confidence and independence. The integration of these two approaches can serve as a conceptual framework for developing student competencies that combine technological literacy, thinking skills, social skills, and character. Therefore, education in the Industrial Revolution 4.0 era should focus on developing students who are adaptive, creative, critical, collaborative, and possess strong character.